A two-part phase 1 study to establish and compare the safety and local tolerability of two nasal formulations of XF-73 for decolonisation of Staphylococcus aureus: A previously investigated 0.5 mg/g viscosified gel formulation versus a modified formulation. (June 2020) - Yendewa, George A.; Griffiss, J. McLeod; Jacobs, Michael R.; Fulton, Scott A.; O'Riordan, Mary Ann; Gray, Wesley A.; Proskin, Howard M.; Winkle, Peter; Salata, Robert A.
Highlights: XF-73 led to a rapid reduction in semiquantitative Staphylococcus aureus scores. Common treatment-related adverse events were rhinorrhoea and nasal dryness. XF-73 demonstrated safety, tolerability and minimal side effects in healthy volunteers. Abstract: Objectives: Successful decolonisation of nasal Staphylococcus aureus (SA) carriage by mupirocin is limited by increasing drug resistance. This randomised, open-label, phase 1 study compared the safety and local tolerability of two nasal formulations of XF-73, a novel porphyrinic antibacterial with rapid intrinsic activity against SA. Methods: The study was performed in 60 healthy adults. In Part 1, eight non-SA carriers were randomised to groups of four subjects each and were treated with XF-73 concentrations of 0.5 mg/g 2% gel or 2.0 mg/g 2% gel. In Part 2, 52 persistent SA carriers were randomised to groups of 13 subjects each and were treated with XF-73 concentrations of 0.5 mg/g 2% gel, 2.0 mg/g 2% gel, 0.5 mg/g 4% gel or 4% viscosified placebo gel. Plasma pharmacokinetic and pharmacodynamic studies were performed. Antistaphylococcal activity was assessed as the presence/absence of SA and by quantification of colonisation using a semiquantitative scale (SA score). Results: 56 subjects (8/8 from Part 1 and 48/52 from Part 2) completed the study, with 47/60 comprising the pharmacokinetic population and 48/60 the pharmacodynamic population. There was no measurable systemic absorption of XF-73. XF-73 treatment was associated with rapid reduction in SA score in all subjects. The most common treatment-emergent adverse events (TEAEs) were rhinorrhoea and nasal dryness (15.5% each in Parts 1 and 2). TEAEs were mild and resolved spontaneously. Conclusion: XF-73 was well tolerated with minimal side effects at doses of 0.5 mg/g 2% gel and 2.0 mg/g 2% gel. These findings support further development of XF-73.